Eficiência da Azospirillum brasilense combinada com doses de nitrogênio no desenvolvimento de plantas de milho - Repke, Rodrigo Alberto [UNESP]; Cruz, Sihélio Júlio Silva [UNESP]; Silva, Carlos Jorge da [UNESP]; Figueiredo, Priscila Gonzales [UNESP]; Bicudo, Silvio José [UNESP] (Revista Brasileira de Milho e Sorgo, 2013)
This study aimed to evaluate the effect of the use of diazotrophic bacterium Azospirillum brasilense inoculated to seeds in combination with nitrogen on the development of corn plants. The experiment was carried out in field using a randomized block design in a double factorial arrangement with four reapplications.. The factor 1: with and without the bacterium application in the seed; and factor 2: six nitrogen doses: 0, 80, 105, 130, 155 and 180 kg ha-1. The trangenic maize hybrid 2B587 Hx was used. The morphological evaluations of plant and ear were done at 20, 40, 60, 80 and 100 days after emergence (DAE). Grain yield was measured at 115 DAE. The application of diazotrophic bacterium Azospirillum brasilense solution via the seeds, with or without synthetic nitrogen did not interfere with plant development and yield of maize. The adoption of this practice does not replace the use of nitrogen fertilizers nor allows dose reduction. The addition of nitrogen fertilizers promotes greater plant growth and increased productivity.

Este trabalho teve como objetivo avaliar o efeito do uso da bactéria diazotrofica Azospirillum brasilense inoculada via sementes em associação com doses de nitrogênio no desenvolvimento de plantas de milho. A pesquisa foi composta por um ensaio com delineamento experimental de blocos ao acaso, com quatro repetições, em esquema fatorial duplo. O fator 1, dois níveis: sem e com aplicação da solução da bactéria Azospirillum brasilense nas sementes; e o fator 2, seis doses totais de nitrogênio: zero, 80, 105, 130, 155 e 180 kg ha-1. As avaliações morfológicas da planta e da espiga foram realizadas aos 20, 40, 60, 80 e 100 dias após a emergência. A aplicação da bactéria diazotrofica Azospirillum brasilense via solução nas sementes, acompanhada ou não de doses de nitrogênio sintético, não interfere no desenvolvimento de plantas e na produtividade da cultura do milho. A adoção desta prática não substitui o uso de fertilizantes nitrogenados e tampouco permite a redução da dose. A adição de fertilizantes nitrogenados promove maior desenvolvimento das plantas, com aumento da produtividade.
Azospirillum brasilense efficiency in combination with doses of nitrogen in the development of maize
Keywords: Zea mays; Biological nitrogen fixation; Nitrogen fertilization; Zea mays; Fixação biológica de nitrogênio; Adubação nitrogenada